EFFECTS OF MITRAL VALVE REPLACEMENT WITH AND WITHOUT CHORDAL PRESERVATION ON CARDIAC FUNCTION: EARLY AND MID-TERM RESULTS - Zakai, Saad Bader; Khan, Salman -Ur-Rehman; Rabbi, Fazle; Tasneem, Habiba (Journal of Ayub Medical College Abbottabad, 2010)
Background: Convention mitral valve (MV) replacement is known to cause deterioration in the left ventricle function, the major mechanism responsible being disruption of the annulo-papillary continuity, thus favoring preservation of the mitral subvalvular apparatus. The aim of this study was to compare the early and midterm results, in terms of cardiac mechanics and clinical outcomes, of preserving the subvalvular apparatus (partial/complete) verses resection during mitral valve replacement. Methods: This was a prospective non randomised trial. One hundred and twenty-two patients (mean age 40.36±14.27 years) admitted for MV replacement from January 2009 to September 2009 were included in the study. They were divided into 3 groups: complete excision of the subvalvular apparatus (group 1=32); preservation of the posterior leaflet (group 2=54) and total chordal preservation (group 3=36). Echocardiography was done preoperatively, at discharge, and at 6 months follow-up. Results: The preservation groups 2, 3 revealed marked improvements with respect to the End-diestolic Volume (EDV) and End-Systolic Volume (ESV) as compared to the non-preservation group 1 at discharge from hospital. At followup, the preservation groups showed improved EDV and ESV in contrast to the non-preservation group, where the ventricular volumes had a declining pattern. Ejection fraction remained below the baseline preoperative level in all three groups at discharge from hospital. In the follow-up, chordal preservation groups showed significant improvements in the ejection fraction as compared to the resection group. An interesting finding was that of PA pressures and LA size between the groups. It was significantly improved in the preservation groups as compared to the resection group. At follow-up, 43.5% of patients in group 1 were in AF compared with 27.5% in group 2 and 21.4% in group 3. More patients in group 1 were in NYHA functional class III or IV at follow-up: 30.4% versus 7.5% and 7.1% respectively. Conclusion: Preservation of the mitral subvalvular apparatus resulted in a greater decrease of ventricular dimensions at discharge which was maintained at follow-up; complete resection resulted in ventricular dilatation at follow-up. Furthermore, the ejection fraction improved in the preservation groups compared to the complete resection group which showed a decline at follow-up. Keywords: Mitral valve, MV preservation, MV replacement, chordal preservation, MV surgery, subvalvular apparatus